Lethal Necrotizing Fasciitis Triggered by Plaster: Case Report and Review of Literature - Jain, Mohit J (J Orthop Case Rep, 2016)
INTRODUCTION: Plasters have been frequently associated with known complications such as infection, and compartment syndrome or deep vein thrombosis. However, life-threatening complication of necrotizing fasciitis (NF) has not been frequently attributed to plaster. CASE REPORT: We had a case of a 62-year male developing a lethal NF triggered by a below knee plaster for undisplaced fracture medial malleolus after twisting injury. He had no history suggestive of diabetes, renal impairment, and predisposing allergic factors or any comorbidity. Despite early diagnosis and aggressive management with above knee amputation, death occurs due to septic shock on the 20(th) day. A similar case of reported lethal NF triggered by plaster has also been reviewed in this report. CONCLUSION: This case highlights a life-threatening rare complication of plaster and author recommends thorough clinical history taking, precleaning of limb, use of sterile water and use of adequate wrap around skin for gypsum plasters as prevention apart from high index of suspicion for early diagnosis, and rapid management.